Search for fast radio transients using Arecibo drift-scan observations at 1.4 GHz. Issue 2 (30th October 2021) - Perera, B B P; Smith, A J; Vaddi, S; Carballo-Rubio, R; McGilvray, A; Venkataraman, A; Roshi, D Anish; Manoharan, P K; Perillat, P; Lieb, E; Lorimer, D R; McLaughlin, M A; et al.
ABSTRACT: We conducted a drift-scan observation campaign using the 305-m Arecibo telescope in 2020 January and March when the observatory was temporarily closed during the intense earthquakes and the initial outbreak of the COVID-19 pandemic, respectively. The primary objective of the survey was to search for fast radio transients, including fast radio bursts (FRBs) and rotating radio transients (RRATs). We used the seven-beam ALFA receiver to observe different sections of the sky within the declination region ∼(10°–20°) on 23 nights and collected 160 h of data in total. We searched our data for single-pulse transients, of covering up to a maximum dispersion measure of 11 000 pc cm −3 at which the dispersion delay across the entire bandwidth is equal to the 13-s transit length of our observations. The analysis produced more than 18 million candidates. Machine learning techniques sorted the radio frequency interference and possibly astrophysical candidates, allowing us to visually inspect and confirm the candidate transients. We found no evidence for new astrophysical transients in our data. We also searched for emission from repeated transient signals, but found no evidence for such sources. We detected single pulses from two known pulsars in our observations and their measured flux densities are consistent with the expected values. Based on our observations and sensitivity, we estimated the upper limit for the FRB rate to be <2.8 × 10 5  sky −1  d −1 above a fluence of 0.16 Jy ms at 1.4 GHz, which is consistent with the rates from other telescopes and surveys.